2015
DOI: 10.4236/gep.2015.39004
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Livestock Grazing on Soil Characteristics in Mount Kilimanjaro, Tanzania

Abstract: Livestock grazing is an anthropogenic disturbance on the soil properties in montane forests of the northern slopes of Mount Kilimanjaro. It was determined the effect of livestock grazing on SOC, N, CEC, SAS, SFD and P in the montane forest. Forty plots were randomly established for collection of soil samples. Data showed livestock grazing decreased the accumulation of SOC and consequently negatively affected the natural pattern of N, P, SFD, CEC and SAS. An opposing pattern of available soil phosphorus was int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Inverted J shape pattern is normal population structure and shows the existence of species in healthier condition. Similar results were reported by (Abate et al 2006;Haile et al, 2008;Ermias et al, 2008;Leul et al, 2010;Samson et al, 2010;Tesfaye et al, 2013;Kflay and Kitessa, 2014;Mligo., 2015;Tesfaye et al, 2017b;and Tesfay et al, 2019).…”
Section: Woody Species Structuresupporting
confidence: 83%
See 1 more Smart Citation
“…Inverted J shape pattern is normal population structure and shows the existence of species in healthier condition. Similar results were reported by (Abate et al 2006;Haile et al, 2008;Ermias et al, 2008;Leul et al, 2010;Samson et al, 2010;Tesfaye et al, 2013;Kflay and Kitessa, 2014;Mligo., 2015;Tesfaye et al, 2017b;and Tesfay et al, 2019).…”
Section: Woody Species Structuresupporting
confidence: 83%
“…Diameter at breast height (DBH): diameter of woody species arbitrarily arranged in diameter class intervals by referring (Mligo, 2015;Tesfay et al, 2019). Diameter of trees ̸ shrub plant species of KSNP was classified into nine classes of 10cm interval (2.5-10,10.1-20, 20.1-30, 30.1-40, 40.1-50, 50.1-60, 60.1-70, 70.1-80 and >80.1cm).…”
Section: Data Analysis a Woody Species Structurementioning
confidence: 99%
“…That livestock activities, including grazing, egestion and excretion, and trampling affect the structure and functioning of grassland ecosystems has led some workers to suggest that grazing and animal agriculture are ecologically destructive (Belsky, 1987;Mligo, 2015). Logic, however, causes one to question that notion, and numerous studies, both empirical and model-based, have demonstrated that a multiplicity of geophysical, biological, behavioral, and natural historical factors, functioning over seasonal to evolutionary timescales influence the ways that wild and domesticated grazers affect grassland ecosystems (McNaughton, 1985;Milchunas et al, 1988;Milchunas and Lauenroth, 1993;Cingolani et al, 2005;Patra et al, 2005;Villalba and Provenza, 2009;Hilario et al, 2017).…”
Section: Impacts To Plant Communities and Soil Healthmentioning
confidence: 99%
“…The number of total species recorded in Kafta-sheraro national park (182 species) was higher than other areas of the country like Alemsaga:124 species (Getinet et al The highest Shannon -Wiener diversity index and evenness in the study area were (H'= 2.82, J=0.72) which is comparable with other Ethiopian forests.Yemrehane Kirstos Church: H'=2.88, J=0.79 (Amanuel and Gemedo, 2018); Berbere: H'=2.95, J=0.76 (Tesfaye et al, 2017a); Tara Gedam: H' = 2.98, J=0.65 (Haileab et al, 2011); Doshke: H'=3.04, J=0.85 (Ayalew et al, 2018). But diversity index is higher than Grat-Kahsu protected dry natural vegetation of Tigray region: H'=2.38 (Tesfay et al, 2019) and H'=2.4: (Mligo, 2015). Diversity indices provide more information about community composition than simply species richness by taking into account relative abundance of different species (Giliba et al, 2011).…”
Section: Vegetation Composition and Diversity Of The Study Areamentioning
confidence: 99%